PERANAN K.H. IMAM BULQIN SEBAGAI PEJUANG DALAM MENENTANG KEMBALINYA PENJAJAHAN BELANDA DI BENGKALIS (1935-1949) - Dzaki 'ilma; Bunari; Asril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This type of research is historical research, which is a research method that aims to make a systematic and objective reconstruction of the past by collecting evidence to establish facts and obtain strong conclusions. This research was carried out in Bengkalis Regency by reaching various relevant locations, such as the Bengkalis Regency Library and Archives Office, the Soeman HS Regional Library in Pekanbaru, the Riau Provincial Archives Office, and the homes of resource persons in the Bengkalis area. The data collection techniques used include observation, interviews, documentation, and literature studies. The data analysis technique in this study is a systematic process carried out from the beginning to the end of the research to process, study, and compile data obtained from observations, interviews, and documentation inductively. K.H. Imam Bulqin is an influential scholar from Bengkalis who has a strategic role in the fields of da'wah, Islamic education, and the struggle for independence. The education he took at various Islamic boarding schools in Java and the experience of migrating to Malaysia formed a broad Islamic insight while instilling a strong spirit of nationalism. Upon his return to Bengkalis, he was warmly welcomed by the community for his contribution in guiding socio-religious life, spreading Islamic teachings, and becoming a moral and spiritual role model. The period 1935-1949 was the most dynamic period in his work, when the political situation was colored by Dutch colonialism, Japanese occupation, and post-proclamation military aggression. The findings of this study confirm that the role of scholars such as K.H. Imam Bulqin proves that the struggle for Indonesian independence is not only carried out by military figures and politicians, but also by religious leaders who have the capacity to awaken the collective consciousness of the nation.